Representasi Indonesia Baru dalam Logo Pohon Hayat Nusantara (Analisis Semiotika Peirce) - Fadilah Nurul Hayati; Ashabul Yamin Asgha (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2026)
The development of the Capital City of Nusantara carries the narrative of "New Indonesia" that needs to be communicated visually to the public. The "Pohon Hayat Nusantara" logo was established as the main visual identity, but the symbolic meaning contained within it has not been studied in depth from the perspective of visual communication. The purpose of this study is to determine how the representation of "New Indonesia" is constructed visually through the Pohon Hayat Nusantara logo. This study uses a constructivist paradigm with qualitative methods. The data analysis technique uses Charles Sanders Peirce's semiotics focusing on the three triadic elements: representamen, object, and interpretant. Data collection techniques were carried out through literature studies and documentation of the Visual Identity Guidelines of IKN Number 54 of 2023.The results show that the 5 roots in the logo represent Pancasila as the foundation of the state, 7 trunks represent the diversity of the 7 major regions of Indonesia, and 17 petals represent the spirit of independence on August 17, 1945. The use of brown represents harmony with the nature of Kalimantan, black represents sovereignty, and white represents a clean vision. The "IKN Sutasoma" typography represents the relationship between the cultural heritage of Nusantara and the face of modern government. Overall, the Pohon Hayat Nusantara logo functions as a state communication tool that constructs the meanings of sustainability, unity, and the aspiration of "New Indonesia" that is inclusive and future-oriented.